(untitled) (African Journal of Biomedical Research, 2023)
The effect of acute oral cadmium (Cd) exposure on testicular oxidative and antioxidant status of adult Wistar rats was investigated. Twenty male rats of comparable weight (130-160g) were assigned to 4 groups (three tests and a control; n = 5). The Cd-exposed groups consumed drinking water contaminated with CdCl2 in concentrations of 10ppm, 100ppm and 1000ppm for 7 days. At the end of exposure, blood samples and the testes were obtained for assessment of blood Cd level, serum testosterone, testicular tissue oxidation and antioxidant levels as well as histology. Significant increase in blood Cd level was noticed in the 100ppm (0.0153±0.0085ppm) and 1000ppm (0.0298±0.0204ppm) exposed groups compared to control (0.0008±0.0005ppm). Acute Cd-exposure causes a dose-dependent significant decrease in percentage body weight gain, serum testosterone but a non-significant increase in testicular weight. There was a significant dose-dependent increase in testicular malondialdehyde (6.52±1.06 vs 10.78±0.43 vs 16.74±1.76 vs 24.06±0.98) u/mg protein but a decrease in superoxide dismutase (76.74±5.49 vs 62.39±1.58 vs 40.02±5.48 vs 25.92±3.06) u/mg protein and catalase (245.66±23.85 vs 216.75±12.61 vs 117.11±13.05 vs 68.61±4.36) u/mg protein activities. These may indicate that acute exposure can adversely affect the testes through stimulation of testicular oxidation and inhibition of the antioxidant system to cause a decrease in testosterone production.